Non-surgical treatment of locally advanced thymic epithelial tumors—a need for multicenter trials - Roden, Anja C. (Journal of Thoracic Disease, 2016)
Thymic epithelial tumors (TET) are rare neoplasms that usually occur in the prevascular mediastinum. Complete resection has been shown to be a favorable prognostic parameter for TET (1-4). Resectability of these tumors usually depends on their size and stage with reported rates of complete resection ranging between 100% for Masaoka stage I and 0–78% for stage IV tumors (1,3).